Evaluation of Factors Influencing Passengers' Interest in Ticket Purchase Decision for the KM. Kirana 1 Ship on the Sampit Route - Muhamad Hikam Firdaus; Sulistyowati Sulistyowati; Andar Sri Sumantri (Shipping and Transport Management Journal, 2025)
This study aims to evaluate the factors influencing passengers’ interest in purchasing tickets for the KM. Kirana 1 ship on the Sampit route. In the era of increasing competition in maritime transportation, understanding consumer interest factors is essential for shipping companies to enhance their marketing strategies and stay competitive. This research employs a quantitative approach using a survey method involving passengers of KM. Kirana 1. The variables examined in this study include price, service quality, promotion, and perceived comfort, which are considered key determinants in customer decision-making. Data were analyzed using SPSS to test validity, reliability, and the relationships among these variables. The results indicate that price, service quality, and comfort significantly affect passengers’ interest in purchasing tickets, while promotion has an insignificant effect. These findings provide practical implications for shipping management to improve service quality, comfort, and pricing strategies to maintain customer satisfaction and loyalty, which are critical in the highly competitive maritime industry.